Gross chemical composition of three common macroalgae and a sea grass on the Pacific coast of Baja California, Mexico - Serviere-Zaragoza, Elisa; Gómez-López, Dalia; Ponce-Díaz, Germán (HIDROBIOLÓGICA, 2017)
Chemical composition (moisture, crude protein, crude fibre, ether extractables, ash, and nitrogen-free extract) was determined in three marine algae and one sea grass of the Pacific coast of Baja California Sur. Samples of Eisenia arborea, Macrocystis pyrifera, Gelidium robustum and Phyllospadix torreyi from natural populations were evaluated in October 1995, and January, May and August 1996. Nitrogen-free extract, mainly carbohydrates, was the most important constituent in all specie, followed b ash, protein, crude fibre, and ether extractables (mainly lipids) in broen algae species. In red algae, protein content was higher than ash. Sea grass (P. torreyi) had high crude fibre, followed by ash, protein, and ether extractables.